Tunable CO Dissociation Assisted by H2 over Cobalt Species: A Mechanistic Study by In‐situ DRIFTS. Issue 23 (20th October 2021) - Shi, Kangzhong; Guo, Lisheng; Zhang, Wei; Jiang, Yong; Li, Da; Liu, Kai; Li, Mengmeng; Xue, Zhaoming; Sun, Song; Mao, Changjie
Abstract: Fischer‐Tropsch synthesis (FTS) is an important heterogeneous catalytic process that can effectively reduce human dependence on the non‐renewable petroleum resources. Cobalt is a crucial active metal center in most catalysts, which effectively catalyzes syngas into valuable products such as liquid fuels. On this basis, we systematically investigated the adsorption of CO on the surface of different cobalt species and its dissociation characteristics assisted by H2 are studied by the in‐situ DRIFTS. For the metallic cobalt phase, H2 ‐assisted CO dissociation not only possessed the FTS activity, but also inhibited the CO disproportionation reaction. However, for the CoO phase, the bidentate carbonate species were decomposed into CO2 . In addition, CoO presented a high‐chain propagation ability than that of Co under the same operation conditions. Co2 O3 and Co3 O4 also exhibited similar CO dissociation patterns with the assistance of H2 . However, different from CoO phase, formate species also formed under the H2 atmosphere over these two Co species. In summary, CO dissociation would be well tuned via the assistance of H2 as demonstrated by the in‐situ DRIFTS. This work provides a new sight on the rational design of efficient cobalt catalysts toward the FTS processes. Abstract : Tunable CO Dissociation : H2 ‐assisted CO dissociation over different cobalt phases (Co, CoO, Co2 O3, Co3 O4 ) were systematically investigated via the in‐situ DRIFTS. H2 ‐assisted CO dissociation is closely related to the metal phase, and the CO dissociation could be well regulated via H2 assistance, which will provide a new insight for constructing an efficient cobalt‐based catalyst.